Clinical outcomes after percutaneous or surgical revascularisation of unprotected left main coronary artery-related acute myocardial infarction: a single-centre experience. Issue 10 (28th March 2013) - Grundeken, Maik J; Vis, M Marije; Beijk, Marcel A M; Kikkert, Wouter J; Damman, Peter; Kloek, Jaap J; Baan, Jan; Koch, Karel T; Wykrzykowska, Joanna J; Tijssen, Jan G P; de Mol, Bas A J M; Henriques, Jose P S; et al.
Abstract : Objectives: We evaluated 30-day and 1-year clinical outcomes after percutaneous or surgical coronary revascularisation in patients with unprotected left main coronary artery (ULMCA)-related acute myocardial infarction (AMI). Design: Single-centre registry. Patients: Between January 1998 and December 2008, 84 patients with ULMCA-related AMI underwent revascularisation treatment in our institution (55 underwent percutaneous coronary intervention (PCI), 29 underwent coronary artery bypass graft surgery (CABG)). Methods: One-year clinical follow-up was obtained for all patients. Univariable and multivariable analyses were performed to find predictors for 30-day mortality and treatment allocation. Results: In the PCI-group, all-cause mortality was 64% at 30 days and 69% at 1 year. In the CABG-group, this was 24% at 30 days and 1 year. Independent predictors of 30-day mortality were cardiogenic shock (HR 2.83), thrombolysis in MI (TIMI) 0/1 flow (HR 2.27) and diabetes mellitus (HR 2.65). Treatment allocation to PCI was primarily determined by TIMI 0/1 flow on baseline angiogram (OR 150). In patients with TIMI 2/3 flow on initial angiogram, treatment allocation was determined by presentation with cardiogenic shock (OR 5.61), year of inclusion (OR 1.72), and distal/bifurcation disease (OR 0.11). Conclusions: Thirty-day mortality was high in patients presenting with an ULMCA-related AMI, both in the PCI as in the CABG-treatment group. Presentation with cardiogenic shock, TIMI 0/1 flow on initial angiogram and diabetes mellitus were independently predicting of 30-day mortality, whereas treatment allocation was primarily determined by presentation with TIMI 0/1 flow.